Changes in North Korea's higher education and education management system during the Kim Jong Un Era. Issue 2 (3rd April 2021) - Kim, Eun-Jeong
ABSTRACT: This study aimed to review changes in North Korea's education system during the Kim Jong-un era to determine if North Korea has focused on higher education and obtained the educational goals set in the Kim Jung-il era. To do so, this paper examines how North Korea's education laws and educational content have influenced its central educational administration system from the Kim Il-sung to the Kim Jong-un regime. This study also explores specific changes in North Korea's higher education system. For the analysis, I reviewed a variety of documents and media content, such as policies announced by the North Korean media, statute books, textbooks, magazines, and interviews with North Korean defectors regarding educational changes. Results indicate that North Korea's educational system was reformed only after the reform of its administrative system. Additionally, the results demonstrate that North Korean education has shifted from basic, theoretical education to practical education during the Kim Jong-un regime. This study concludes that higher education in North Korea will continue to be reinforced for everyone so it can build an advanced nation.